Insights on the Reactivity of Terminal Phosphanido Metal Complexes Toward Activated Alkynes from Theoretical Computations - Cardenas-Jiron, G; Mera-Adasme, R (American Chemical Society, 2017)
Herein we present a theoretical study on the reaction of [Re(PPh2) (CO)3(phen)] (phen = 1,10-phenanthroline) and [Re(PPh2) (CO)3(bipy)] (bipy = 2,2′-bipyridine) toward methyl propiolate. In agreement with experimental results for the phen ligand, the coupling of the substituted acetylenic carbon with the nonsubstituted ortho carbon of the phen ligand is the preferred route from both kinetic and thermodynamic viewpoints with a Gibbs energy barrier of 18.8 kcal/mol and an exoergicity of 11.1 kcal/mol. There are other two routes, the insertion of the acetylenic fragment into the P-Re bond and the coupling between the substituted acetylenic carbon and a carbonyl ligand in cis disposition, which are kinetically less favorable than the preferred route (by 2.8 and 1.9 kcal/mol, respectively). Compared with phen, the bipy ligand shows less electrophilic character and also less π electron delocalization due to the absence of the fused ring between the two pyridine rings. As a consequence, the route involving the coupling with a carbonyl ligand starts to be kinetically competitive, whereas the product of the attack to bipy is still the most stable and would be the one mainly obtained after spending enough time to reach thermal equilibrium. © 2017 American Chemical Society.